Оцінка енергоємності глибокого обробітку ґрунту комбінованими чизельними глибокорозпушувачами - Лещенко, С. М.; Сало, В. М.; Петренко, Д. І.; Лещенко, С. Н.; Петренко, Д. И.; Leshchenko, S.; Salo, V.; Petrenko, D. (ЦНТУ, 2018)
В роботі проводиться оцінка енергоємності основного обробітку ґрунту комбінованими чизельними глибокорозпушувачами. Доводиться, що незважаючи на значну кількість досліджень у напрямку скорочення витрат енергії на основний обробіток ґрунту, питання залишається актуальним, а з врахуванням необхідності впровадження ґрунтозахисних технологій, найбільш доцільним є оптимізація енерговитрат при проведенні безполицевого обробітку ґрунту комбінованими чизельними ґлибокорозпушувачами. В результаті проведених досліджень доведено можливість скорочення енерговитрат на основний обробіток ґрунту при використанні комбінованих чизельних глибокорозпушувачів із додатковими деформаторами за умови їх ефективного агрегатування з енергетичними засобами. Спираючись на результати практичного використання таких агрегатів розроблені рекомендації щодо їх подальшого використання та вдосконалення В работе проводится оценка энергоемкости основной обработки почвы комбинированными чизельными глубокорыхлителями. Доказывается, что несмотря на значительное количество исследований в направлении сокращения затрат энергии на основную обработку почвы, вопрос остается актуальным, а с учетом необходимости внедрения почвозащитных технологий, наиболее целесообразным является оптимизация энергозатрат при проведении безотвальной обработки почвы комбинированными чизельными глубокорыхлителями. В результате проведенных исследований, доказана возможность сокращения энергозатрат на основную обработку почвы при использовании комбинированных чизельных глубокорыхлителей с дополнительными деформаторами, при условии их эффективного агрегатирования с энергетическими средствами. Опираясь на результаты практического использования таких агрегатов, разработаны рекомендации по их дальнейшему использованию и усовершенствованию The work presents the assessment of energy intensity of the basic soil cultivation with combined chisel deep tillers. It is proved that despite a significant amount of research in the sphere of reducing energy consumption for basic soil cultivation, the issue remains relevant, and taking into account the necessity to apply soil protection technologies, the optimization of energy consumption in the process of subsoil tillage with combined chisel deep tillers becomes most significant. At the stage of the analysis of the conducted studies it has been confirmed that the most effective indicator of the assessment of energy expenditure for soil cultivation is the consumption of fuel, and the change in the geometrical parameters of the working parts is inevitably connected with the dilemma "traction resistance - quality of cultivation". It is clear that reducing traction resistance, as a rule, leads to the deterioration in the quality of soil cultivation and vice versa. Therefore, when designing soil cultivating machines it is necessary to clearly define their principal characteristics. As a result of the conducted research the possibility of reduction of energy consumption for the basic tillage with the application of combined chisel deep tillers with additional deformers is proved. This happens under the condition of effective aggregation with energy means. Based on the results of practical use of such units, recommendations for their further use and improvement were developed. Chisel tillers CHN of domestic production, working bodies of which have chisel paws with flat wings and teeth and dual gears, while working on complicated soils of central Ukraine with an average fuel consumption of about 18 l/ha, at a depth of 35 cm or more ensure the qualitative index of soil crush is 70 ... 75%.
Оценка энергоемкости глубокой обработки почвы комбинированными чизельными глубокорыхлителями
Assessment of Energy Intensity of Deep Cultivation of Soil by Combined Chisel Deep Tillers
Keywords: ґрунтозахисні технології; енергоємність обробітку ґрунту; комбінований чизельний глибокорозпушувач; витрати пального; тяговий опір; энергоемкость обработки почвы; тяговое сопротивление; почвозащитные технологии; комбинированный чизельный глубокорыхлитель; расход топлива; energy intensity of soil tillage; soil protection technologies; combined chisel deep tiller; fuel consumption; traction resistance